Peranan wanita dalam penjagaan alam sekitar melalui penerapan nilai dan etika - Syed Hussain, Tuan Pah Rokiah; Ismail, Hamidi; Yusof, Rohana; Syed Ibrahim, Sharifah Sofiah 'Atiqah (2013)
Adoption of values and environmental ethics in accordance with The good principles should be, sown in human to ensure environmental sustainability.This is because, by understanding and implementing the values and ethics of environmental stewardship only that will ensure the well-being and survival of future generations. In addition, the quality of human life will also increase in line with increasing environmental quality.Therefore, this paper aims to discuss the concept of the role of women through the adoption of ethical values and environmental stewardship at all levels whether at home, neighborhood, workplace and country.Contribution of women in the care of the environment it is clear that through efforts such as education, awareness and love for the environment among family members especially children and can transform social attitudes begin at home, neighbors and colleagues.Conceptual study using content analysis also focuses on the principles of values and environmental ethics that can serve as a guide for human for consideration when dealing with the environment, other people or with other earth creatures.Values and ethical principles can also be a guide for human to make changes in the social, political and economic with emphasis on the environment. With the advent of this writing, hopefully can give these ideas lo create awareness among the women as a reflection of environment care and can be manage of trust's and good responsibility as possible for the sake of environmental sustainability and world peace.